Histone Deacetylases with Antagonistic Roles in Saccharomyces cerevisiae Heterochromatin Formation - Thurtle-Schmidt, Deborah M; Dodson, Anne E; Rine, Jasper (Genetics (Austin), 2016)
As the only catalytic member of the Sir-protein gene-silencing complex, Sir2’s catalytic activity is necessary for silencing. The only known role for Sir2’s catalytic activity in Saccharomyces cerevisiae silencing is to deacetylate N-terminal tails of histones H3 and H4, creating high-affinity binding sites for the Sir-protein complex, resulting in association of Sir proteins across the silenced domain. This histone deacetylation model makes the simple prediction that preemptively removing Sir2’s H3 and H4 acetyl substrates, by mutating these lysines to unacetylatable arginines, or removing the acetyl transferase responsible for their acetylation, should restore silencing in the Sir2 catalytic mutant. However, this was not the case. We conducted a genetic screen to explore what aspect of Sir2’s catalytic activity has not been accounted for in silencing. Mutation of a nonsirtuin histone deacetylase, Rpd3, restored Sir-protein-based silencing in the absence of Sir2’s catalytic activity. Moreover, this antagonism could be mediated by either the large or the small Rpd3-containing complex. Interestingly, this restoration of silencing appeared independent of any known histone H3 or H4 substrates of Rpd3. Investigation of Sir-protein association in the Rpd3 mutant revealed that the restoration of silencing was correlated with an increased association of Sir proteins at the silencers, suggesting that Rpd3 was an antagonist of Sir2’s function in nucleation of Sir proteins to the silencer. Additionally, restoration of silencing by Rpd3 was dependent on another sirtuin family member, Hst3, indicating multiple antagonistic roles for deacetylases in S. cerevisiae silencing.